Ventilation inhomogeneity in children with primary ciliary dyskinesia - Green, Kent; Buchvald, Frederik F; Marthin, June Kehlet; Hanel, Birgitte; Gustafsson, Per M; Nielsen, Kim Gjerum (Thorax, 2012)
BackgroundThe lung clearance index (LCI) derived from the multiple breath inert gas washout (MBW) test reflects global ventilation distribution inhomogeneity. It is more sensitive than forced expiratory volume in 1 s (FEV1) for detecting abnormal airway function and correlates closely with structural lung damage in children with cystic fibrosis, which shares features with primary ciliary dyskinesia (PCD). Normalised phase III slope indices Scond and Sacin reflect function of the small conducting and acinar airways, respectively. The involvement of the peripheral airways assessed by MBW tests has not been previously described in PCD.MethodsA cross-sectional MBW study was performed in 27 children and adolescents with verified PCD, all clinically stable and able to perform lung function tests. LCI, Scond (n=23) and Sacin (n=23) were derived from MBW using a mass spectrometer and sulfur hexafluoride as inert marker gas. MBW indices were compared with present age, age at diagnosis and spirometry findings, and were related to published normative values.ResultsLCI, Scond and Sacin were abnormal in 85%, 96% and 78% of patients with PCD and in 81%, 93% and 79%, respectively, of 13/27 subjects with normal FEV1. LCI and Sacin correlated significantly while Scond did not correlate with any other lung function parameters. None of the lung function measurements correlated with age or age at diagnosis.ConclusionsPCD is characterised by marked peripheral airway dysfunction. MBW seems promising in the early detection of lung damage, even in young patients with PCD. The relationship of MBW indices to the outcome of long-term disease and their role in the management of PCD need to be assessed.